Comparative Study on Electroanalysis of Fenthion Using Silver Amalgam Film Electrode and Glassy Carbon Electrode Modified with Reduced Graphene Oxide - Smarzewska, Sylwia; Metelka, Radovan; Festinger, Natalia; Guziejewski, Dariusz; Ciesielski, Witold (Wiley-VCH, 2017)
Oxidation and reduction processes of the insecticide fenthion was comparatively investigated at a reduced graphene oxide modified glassy carbon electrode (RGO-GCE) and a cyclic renewable silver amalgam film electrode (Hg(Ag)FE) using square wave stripping voltammetry (SWSV). The influence of pH and SW parameters was investigated. The linear concentration ranges were found to be 1 x 10(-6) - 2 x 10(-5) and 1 x 10(-7) - 2 x 10(-5) mol L-1 for Hg(Ag)FE and RGO-GCE, respectively. The detection and quantification limits were calculated as 1.3 x 10(-7) and 4.5 x 10(-7) mol L-1 for Hg(Ag)FE and 7.6 x 10(-9) and 2.5 x 10(-8) molL(-1) for RGO-GCE. Both of the developed electroanalytical methods offer rapid and simple detection of fenthion and were used on spiked tap and river water and apple juice samples. Scanning electron microscopy was used for RGO-GCE surface characterization.
Srovnávací studie elektroanalýzy fenthionu s použitím stříbrné amalgámové filmové elektrody a elektrody ze skelného uhlíku s redukovaným oxidem grafenu
Keywords: Fenthion; glassy carbon; silver amalgam electrode; voltammetry; scanning electron microscopy; reduced graphene oxide; Fenthion; skelný uhlík; elektroda ze stříbrného amalgámu; voltametrie; rastrovací elektronová mikroskopie; redukovaný oxid grafenu